Cell-mediated fiber recruitment drives extracellular matrix mechanosensing in engineered fibrillar microenvironments - Baker, Brendon M. (Nat Mater, 2015)
To investigate how cells sense stiffness in settings structurally similar to native extracellular matrices (ECM), we designed a synthetic fibrous material with tunable mechanics and user-defined architecture. In contrast to flat hydrogel surfaces, these fibrous materials recapitulated cell-matrix interactions observed with collagen matrices including stellate cell morphologies, cell-mediated realignment of fibers, and bulk contraction of the material. While increasing the stiffness of flat hydrogel surfaces induced mesenchymal stem cell spreading and proliferation, increasing fiber stiffness instead suppressed spreading and proliferation depending on network architecture. Lower fiber stiffness permitted active cellular forces to recruit nearby fibers, dynamically increasing ligand density at the cell surface and promoting the formation of focal adhesions and related signaling. These studies demonstrate a departure from the well-described relationship between material stiffness and spreading established with hydrogel surfaces, and introduce fiber recruitment as a novel mechanism by which cells probe and respond to mechanics in fibrillar matrices.